Analysis of Public Knowledge on Household Waste Management in Batu Gajah Subdistrict, Sirimau District, Ambon City - Maria Maessy Farneubun; Johan Riry; Ferdinand Salomo Leuwol (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
This study analyzes public knowledge regarding household waste management in Batu Gajah Subdistrict, Sirimau District, Ambon City. In the context of increasing household waste volume due to population growth and economic activities, this study aims to assess the public's understanding of the importance of waste separation and recycling. A descriptive research method was used, with a sample representing 10% of the total population randomly selected from heads of households in each neighborhood unit (RT). Data were collected through observations, questionnaires, and interviews and analyzed using Miles and Huberman's interactive model. The results indicate that most respondents understand the difference between organic and non-organic waste, but knowledge of plastic recycling techniques and composting still needs to be improved. Additionally, most of the community is aware of the negative environmental impacts of burning waste, although practices related to electronic waste management remain minimal. This study highlights the need to improve education and public participation in waste management through collaboration between local governments and communities.